Biochemical and functional responses of stream invertebrate shredders to post-wildfire contamination. (December 2020) - Pradhan, Arunava; Carvalho, Francisco; Abrantes, Nélson; Campos, Isabel; Keizer, Jan Jacob; Cássio, Fernanda; Pascoal, Cláudia
Abstract: Forests in Mediterranean Europe including Portugal are highly susceptible to wildfires. Freshwaters are often exposed to post-wildfire contamination that contains several toxic substances, which may impose risk to freshwater organisms and ecosystem functions. However, knowledge on the impacts of post-wildfire runoffs from different origins on freshwater biota is scarce. In forest streams, invertebrate shredders have a major contribution to aquatic detrital-based food webs, by translocating energy and nutrients from plant-litter to higher trophic levels. We investigated the leaf consumption behaviour and the responses of oxidative and neuronal stress enzymatic biomarkers in the freshwater invertebrate shredder Allogamus ligonifer after short-term exposure (96 h) to post-wildfire runoff samples from Pinus and Eucalyptus plantation forests and stream water from a burnt catchment in Portugal. Chemical analyses indicated the presence of various metals and PAHs at considerable concentrations in all samples, although the levels were higher in the runoff samples from forests than in the stream water. The shredding activity was severely inhibited by exposure to increased concentrations of post-wildfire runoff samples from both forests. The dose-response patterns of enzymatic biomarkers suggest oxidative and neuronal stress in the shredders upon exposure to increasing concentrations of post-wildfire runoffs. The impacts were more pronounced for the runoffs from the burnt forests. Moreover, the response patterns suggest that the energy from the feeding activity of shredders might have contributed to alleviate the stress in A. ligonifer . Overall, the outcomes suggest that the post-wildfire contamination can induce sublethal effects on invertebrate shredders with impacts on key ecological processes in streams. Graphical abstract: Image 1 Highlights: Post-fire runoffs from forests inhibited shredding activity of stream invertebrates. Biomarker responses indicated oxidative and neuronal stress in shredders. The stress increased with increasing exposure concentrations of post-fire runoffs. Impacts of forest runoffs were more severe in shredders under starvation. Metals and PAHs contributed to the stress induced by post-fire runoffs. Abstract : Feeding behaviour and stress biomarker responses of invertebrate shredders associated with stream ecosystem functions in detrital-based food webs are affected by wildfire runoff origin and composition.